1998
DOI: 10.1124/mol.54.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Estrogen Receptor α and Estrogen Receptor β to Partial Estrogen Agonists/Antagonists

Abstract: The existence of two rather than one estrogen receptor, today characterized as estrogen receptor alpha (ERalpha) and estrogen receptor beta (ERbeta), indicates that the mechanism of action of 17beta-estradiol and related synthetic drugs is more complex than previously thought. Because the homology of amino acid residues in the ligand-binding domain (LBD) of ERbeta is high compared with those amino acid residues in ERalpha LBD, previously shown to line the ligand binding cavity or to make direct contacts with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
439
2
9

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 719 publications
(472 citation statements)
references
References 37 publications
22
439
2
9
Order By: Relevance
“…In fact, both drugs exhibited a complete antagonist effect on E 2 -mediated stimulation of the FAAH promoter and they did not have any direct effect when given alone. This is in agreement with a previous study reporting that TMX exhibited a pure antagonism in an ERb expressing system [36]. Consistently with these data epiE 2 , which is ineffective at ERs [28,29], had no effect on FAAH expression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, both drugs exhibited a complete antagonist effect on E 2 -mediated stimulation of the FAAH promoter and they did not have any direct effect when given alone. This is in agreement with a previous study reporting that TMX exhibited a pure antagonism in an ERb expressing system [36]. Consistently with these data epiE 2 , which is ineffective at ERs [28,29], had no effect on FAAH expression.…”
Section: Discussionsupporting
confidence: 93%
“…The biological effects of E 2 are mediated by ERa and ERb [36], and it has been previously demonstrated that mouse Sertoli cells express only ERb [3]. By using a ChIP assay with Sertoli cells, we examined the ligand-dependent recruitment of ERb to the faah promoter in vivo, and we found that E 2 increased ERb binding to ERE2/3 promoter sites.…”
Section: Discussionmentioning
confidence: 87%
“…In agreement with previous observations, ERb is poorly activated by E 2 concentrations below 1 nM (Figure 1b) (Barkhem et al, 1998). In contrast, ERa, reaches approximately 50% activation already at 0.01 nM and shows maximal transcriptional activity at 0.1 nM (Figure 1a).…”
Section: Co-expression Of Era and Erb Negatively Influences Transcripsupporting
confidence: 93%
“…Previous studies have indicated that the iso¯avonoid genistein shows a higher a nity for ERb (Barkhem et al, 1998;Kuiper et al, 1997). 293 cells were cotransfected as before with the ERE-reporter plasmid and ERa or ERb expressing plasmids and treated with increasing amounts of genistein.…”
Section: Erb Promotes the Agonistic Effect Of Genisteinmentioning
confidence: 99%
“…To more quantitatively determine the selectivity of KB9520 for ERb over ERa, HEK293 cells, genetically engineered to stably express human ERa and ERb, respectively, were used as described previously. 33 The dose-response curves showed an EC 50 value of 6.7 nM for KB9520 in the HEK293-ERb cells and B4.9 mM for ERa in the HEK293-ERa cells, that is, KB9520 is a highly ERbselective agonist with approximately 700-fold selectivity for ERb over ERa (Supplementary Figure 2C). To test the antiproliferative effect of activated ERb, EG7, Raji and Ramos cells were treated with either E 2 , selective ERa agonist PPT or selective ERb agonists KB9520 or DPN in culture.…”
Section: Estradiol and Selective Erb Agonists Inhibit Growth Of Murinmentioning
confidence: 96%